EVALUASI PROGRAM LITERASI DAN NUMERASI DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN PENDEKATAN CIPP - Fitriani, Fitriani; Rizal, Fahmi; Ambiyar, Ambiyar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to evaluate the literacy and numeracy program implemented in Differential Calculus learning for first-semester students of the Mathematics Education Study Program at Universitas Muhammadiyah Tapanuli Selatan using the CIPP (Context, Input, Process, Product) evaluation model. This research employed an evaluative-descriptive approach. The participants consisted of 30 first-semester students. Data were collected using a CIPP questionnaire with a Likert scale, classroom observations of literacy–numeracy activities, documentation of numeracy-based modules, and literacy–numeracy tests administered as pretest and posttest. Data analysis was conducted using descriptive statistics (mean and percentage) and thematic analysis for observation and documentation data. The findings revealed that the context component was classified as very good, the process and product components were categorized as good, while the input component was rated as fairly good. The test results indicated a meaningful increase in students’ posttest scores compared to pretest scores, suggesting an improvement in students’ literacy and numeracy skills after the program implementation. The novelty of this study lies in the application of the CIPP evaluation model to assess a literacy and numeracy program in a university-level Differential Calculus course, an area that has received limited attention in previous research.